Carrier Formation Dynamics in Prototypical Organic Solar Cells as Investigated by Transient Absorption Spectroscopy. (8th August 2016) - Moritomo, Yutaka; Yonezawa, Kouhei; Yasuda, Takeshi
Abstract : Subpicosecond transient absorption spectroscopy is a powerful tool used to clarify the exciton and carrier dynamics within the organic solar cells (OSCs). In this review article, we introduce a method to determine the absolute numbers of the excitons and carriers against delay time ( t ) only from the photoinduced absorption (PIA) and electrochemically induced absorption (EIA) spectra. Application of this method to rr-P3HT-, PTB7-, and SMDPPEH-based OSCs revealed common aspects of the carrier formation dynamics. First, the temporal evolution of the numbers of the excitons and carriers indicates that the late decay component of exciton does not contribute to the carrier formation process. This is probably because the late component has not enough excess energy to separate into the electron and hole across the donor/acceptor (D/A) interface. Secondly, the spectroscopy revealed that the exciton-to-carrier conversion process is insensitive to temperature. This observation, together with the fast carrier formation time in OSCs, is consistent with the hot exciton picture.